The Challenges faced by Public Sector Governance in implementing e-Procurement System: A Case Study of Education Department of Malacca - Ngatman, N.H.; Alderei, H.S.S; Musa, H. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
Previously, public procurement was conducted through manual process which involve huge of paper and space arrangement. Not to mention cost that incurred throughout the process. However, the evolution of technology together with the environmental insistence, traditional public procurement is no longer relevant. E-procurement has replaced traditional method without putting aside all the policies and circulars in public procurement. This study highlighted the challenges faced by procurement unit in implementing “the new e-procurement” (known as e-perolehan baharu) in early 2018 such as lacking in ICT support and facilities, financial and human resource constraint, inadequate knowledge and technical skills of the system and behaviour of resistant to change. These challenges affected procurement process as a whole, especially the Small and Medium Enterprise (SMEs). This paper concluded that the government should pay more attention towards the preparation of facilities and ICT support prior the implementation of e-perolehan baharu by all agencies and government organizations.